1998
DOI: 10.1103/physrevlett.81.2962
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Self-Ordering of Quantum Nanostructures Grown on Nonplanar Surfaces

Abstract: We present an analytic model that explains the self-ordering of quantum nanostructures grown on nonplanar surfaces. Self-limiting growth in these structures results from the interplay among growthrate anisotropy, curvature-induced capillarity, and, for alloys, entropy of mixing effects. Experimental results on self-limiting organometallic chemical vapor deposition on corrugated surfaces are in quantitative agreement with the model. The implications of the self-limiting growth characteristics on the self-orderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
113
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 21 publications
6
113
0
2
Order By: Relevance
“…The appearance of a self-limiting width along the bottom of the groove, together with the segregation of the most mobile adatom species along the vertical axis (perpendicular to the bottom facet) of the recess, produces two-dimensional lateral carrier confinement. Our model, which focusses exclusively on kinetics, in contrast to previous studies, 11,12 provides a complete explanation of the observed behavior in V-groove recesses (e.g., modulation of the self-limiting profile width and Ga segregation) based on (i) different rates of precursor and adatom surface kinetics on each facet plane and (ii) interfacet mass transport, which accounts for growth rate anisotropy and capillarity.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The appearance of a self-limiting width along the bottom of the groove, together with the segregation of the most mobile adatom species along the vertical axis (perpendicular to the bottom facet) of the recess, produces two-dimensional lateral carrier confinement. Our model, which focusses exclusively on kinetics, in contrast to previous studies, 11,12 provides a complete explanation of the observed behavior in V-groove recesses (e.g., modulation of the self-limiting profile width and Ga segregation) based on (i) different rates of precursor and adatom surface kinetics on each facet plane and (ii) interfacet mass transport, which accounts for growth rate anisotropy and capillarity.…”
mentioning
confidence: 92%
“…Cross-sectional transmission electron microscopy (TEM) 11 has demonstrated the presence of a transient regime during which the profile of the recess and the Ga segregation evolve toward stationary values determined by the growth conditions and alloy composition. We reproduce the experimentally observed geometric and compositional transients based on reaction-diffusion equations for each facet of the V-groove template, and we explain our results in terms of the surface kinetics established by the geometry and growth conditions.…”
mentioning
confidence: 99%
“…[4][5][6] A variety of theoretical and experimental work has been performed to improve the quality of V-groove and ridge-type QWires and QDots. 7 Both techniques rely on sharp corners or tips and, hence, relatively deep ͑typically several hundreds of nanometers͒ patterns, which are rounded in the case of V-grooves and sharpened in the case of ridges due to adatom migration from the adjacent slow-growing side facets towards the corners or tips for QWire and QDot formation. This requires reshaping of the pattern during growth of the buffer and barrier layers with considerable thickness for well-defined QWire and QDot formation and stacking in multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 Their distinctive V-shaped cross section (typically having sub-μm width) is defined by two mirroring {111}A crystal planes, exposed by the etching procedure. Due to a combination of growthrate anisotropy, curvature-induced capillarity, and entropy of mixing effects, [21][22][23] MOCVD of a thin layer of InGaAs on a GaAs substrate patterned with V grooves results in the formation of a QWR along the main axis of each groove. Figure 1(a) displays a sketch of the grown QWR structure, characterized by a crescent-shaped cross section.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Such V grooves are relatively long (up to several hundreds of microns) linear recesses, oriented along the [110] crystallographic direction and obtained through a combination of electron-beam lithography and wet chemical etching. 15,18 Their distinctive V-shaped cross section (typically having sub-μm width) is defined by two mirroring {111}A crystal planes, exposed by the etching procedure.…”
Section: Introductionmentioning
confidence: 99%